Impact of β-Turn Sequence on β-Hairpin Dynamics Studied with Infrared-Detected Temperature Jump. Issue 5 (11th July 2012) - Popp Popp, Alexander Alexander; Wu Wu, Ling Ling; Keiderling Keiderling, Timothy A. Timothy A.; Hauser Hauser, Karin Karin
Abstract : Folding dynamics for β -structure loss and disordered structure gain were studied in a model β -hairpin peptide based on Cochran's tryptophan zipper peptide Trpzip2, but with an altered Thr-Gly (TG) turn sequence, that is, SWTWETG KWTWK, using laser-induced temperature-jump (T-jump) kinetics with IR detection. As has been shown previously, the TG turn sequence reduces the thermodynamic β -hairpin stability as compared to the Asn-Gly sequence used in Trpzip2 (TZ2-NG). In this study, we found that the TG-turn slows down the overall relaxation dynamics as compared to TZ2-NG, which were studied at higher temperatures where the time constants show little difference between relaxation of the β -strand and the disordered conformation. These time constants become equivalent at lower temperatures for TZ2-TG than was seen for TZ2-NG. The correlation of thermodynamic stability and rates of relaxation suggests that the change from NG to TG turn results in a slowing of folding, lowerk f, with less change of the unfolding rate, k u, assuming two state behavior at higher temperatures.